The utility of radiopharmaceutical uptake in the bladder neck and prostate on preoperative FDG PET/CT in determining urethral surgical margin positivity in patients undergoing radical cystoprostatectomy for bladder cancer - Aydin, Resat; Ergul, Rifat Burak; Tantekin, Anil; Sanli, Yasemin; Erdem, Selcuk; Sanli, Mehmet Oner; Ozcan, Faruk (Bmc, 2025)
BackgroundBladder cancer is the most common malignancy of the urinary system. It is a heterogeneous type of cancer with a high potential for metastasis, approximately 25% of which occurs as muscle invasive. As with other malignancies, accurate and precise staging of bladder cancer is one of the mainstays for choosing the most appropriate treatment for the patient. Detection of metastasis is extremely important in choosing the treatment strategy. FDG PET/CT is widely used in the clinical management of various malignancies and is increasingly used in the primary staging of muscle-invasive bladder cancer and detection of recurrence after radical cystectomy. We aimed to determine the role of radiopharmaceutical uptake in the bladder neck and prostate region in preoperative FDG PET/CT in patients with muscle-invasive bladder tumors in determining the positivity of prostatic urethra surgical margins in the final pathology after cystectomy and its effect in determining the type of diversion to be chosen.MethodsThe data of male patients who underwent FDG PET/CT before radical cystectomy due to MIBC between January 2009 and January 2023 in the Department of Urology at Istanbul Faculty of Medicine were retrospectively analyzed. The correlations between the presence of radiopharmaceutical uptake in the bladder neck or prostate in FDG PET CT and the positivity of the prostatic urethra surgical margin in the postoperative final pathology of these patients and the invasion of urothelial carcinoma in the prostate were analyzed.ResultsProstatic urethra surgical margin positivity was detected in 8 of 50 male patients who had FDG PET CT in the preoperative period. Prostatic urethra surgical margin positivity was detected in 5 of 19 patients with bladder neck and prostate region involvement on FDG (p = 0.2554). Prostate involvement was seen on FDG in 6 of 9 patients with urothelial carcinoma invasion into the prostate (p = 0.1492). Prostate adenocarcinoma was observed in the final pathology of 12 patients, and 8 of these patients had FDG uptake (p = 0.106). While no statistically significant relationship was found between the presence of bladder neck and prostate region involvement on FDG and prostatic urethra surgical margin, urothelial carcinoma invasion into the prostate and prostate adenocarcinoma, a statistically significant relationship was observed between the presence of malignancy in the prostate (urothelial carcinoma and/or adenocarcinoma) (p = 0.0189).ConclusionsWhile no statistically significant relationship was found between radiopharmaceutical uptake in the bladder neck and prostate region on preoperative FDG PET CT in CIBC and prostatic urethra surgical margin positivity, urothelial carcinoma invasion into the prostate and the presence of prostate adenocarcinoma; It was found valuable in detecting the presence of malignancy in the prostate (adenocarcinoma/urothelial carcinoma).
Keywords: Muscle-Invasive Bladder Cancer (Mibc); Fdg Pet/Ct; Bladder Neck And Prostate Uptake; Prostatic Urethral Surgical Margin; Urothelial Carcinoma Invasion; Radical Cystoprostatectomy